2019
DOI: 10.1108/ijcma-02-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

The dual effects of task conflict on team creativity

Abstract: Purpose The purpose of this paper is to explore the dual effects of task conflict on team creativity and the role of team-focused transformational leadership (TFL) as a key contingency in the task conflict–team creativity relationship. Design/methodology/approach Data were collected from 325 teams across ten large companies in South Korea. The study tested the hypothesized moderated mediation model using an SPSS macro (PROCESS, Hayes, 2008). Findings Results showed that task conflict is directly and positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 96 publications
6
56
2
2
Order By: Relevance
“…In this way, the team reflexivity was seen to fully mediate the task conflict and team creativity relationship. Although not hypothesized, but in line with the previous research findings, we found support that task conflict is positively related to team creativity, showing that it brings diverse ideas required for team creativity (Jehn & Mannix, 2001;Lee et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this way, the team reflexivity was seen to fully mediate the task conflict and team creativity relationship. Although not hypothesized, but in line with the previous research findings, we found support that task conflict is positively related to team creativity, showing that it brings diverse ideas required for team creativity (Jehn & Mannix, 2001;Lee et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…As far as the practical implications of this study are concerned, the organizations should promote the culture of frequent meeting sessions and different training and development programs for employees to discuss their task issues. Based on our results and in line with some of the previous research findings, which showed that task conflict can enhance team related outcomes, more specifically team creativity (Hu, Chen, Gu, Huang, & Liu, 2017;Lee et al, 2019;Yong et al, 2014), we also suggest supervisors and team leaders to provide enough opportunities and time for team members to reflect upon their tasks and to rethink about it, which may enhance their overall team creativity. Therefore, the managers should not worry about the conflicts in teams unless these conflicts are not transformed into interpersonal conflicts.…”
Section: Practical Implicationssupporting
confidence: 88%
See 1 more Smart Citation
“…Transformational leadership in the team context has been the focus of increased attention (Cai, Jia, & Li, 2017;Chun, Cho, & Sosik, 2016;Dong et al, 2017;Feng, Huang, & Zhang, 2016;Jiang, Gu, & Wang, 2015;Lee, Avgar, Park, & Choi, 2019;Lorinkova & Perry, 2019). Most of these studies rely on the conceptualizations and measures either by Pearce and Sims (2002) or by Podsakoff, MacKenzie, Moorman, and Fetter (1990) and mostly aggregate individual-centric scales of transformational leadership, as opposed to using genuine team-centric measures.…”
Section: Team-centric Transformational Leadershipmentioning
confidence: 99%
“…We observed the theme "Strong social cohesion is an integral part of the iGEM experience" (87%, 13/15; -Quotes 1, 4, 5), but also observed that "Interpersonal conflict was notable and impacted the team dynamics" (67%, 10/15; Quotes 2, 6, 7). This dissonance as illustrated by Quotes 1 and 2 led us to explore the relationship between social cohesion, defined by Dimas et al (2019) as the integration of the members through emotional bonds and a sense of belonging; and conflict, operationalized by Lee et al (2019) as task conflict (i.e., issues with distribution of resources, procedures and policies, and implementation) or relational conflict (i.e., interpersonal and communication issues). 33,34 "Yeah, we tried to create a very social environment.…”
Section: Meta-theme 1: Conflict Challenges Social Cohesionmentioning
confidence: 99%